Chemical variability in the essential oil composition of Salvia hypoleuca, an endemic species from Iran. Issue 5 (2nd September 2016) - Sonboli, Ali; Salehi, Peyman; Gharehnaghadeh, Saman
Abstract: A chemodiversity of Salvia hypoleuca natural populations based on essential oil composition was performed covering the distribution area of the species in Iran. The aerial flowering parts of twenty-one populations of S. hypoleuca from north of Iran were collected, air-dried, hydrodistilled and their essential oils analyzed by GC and GC-MS. A total of sixty-four compounds were identified accounting for 96.3–99.8% of total oil. The most predominant constituents were bicyclogermacrene (1.5–37.3%), ( E )-caryophyllene (2.1–21.7%), β -pinene (2.1–29.8%) and α -pinene (1.4–29.3%). Multivariate statistical analysis based on the percentages of the essential oils compounds was carried out to determine the chemical variation among the studied populations. The results of cluster analysis enabled the identification of three main chemotypes namely: A, viridiflorol, B, β -pinene + α -pinene and C, ( E )-caryophyllene + bicyclogermacrene.